2022
DOI: 10.1002/pc.26904
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis and theoretical studies on the axial compression behavior of multi‐cell Al‐CFRP hybrid tubes

Abstract: To find a thin‐walled impact‐resistant structure with excellent crushing performance, a multi‐cell hybrid thin‐walled tube (MCHT) formed by winding carbon fibers around a multi‐cell Al tube was proposed. The structure is designed based on different structural parameters of the thin‐walled tubes exhibiting different crushing characteristics and damage modes. First, a finite element model applicable to MCHT is established, and the accuracy of the model is verified by quasi‐static axial pressure experiments. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It was observed that the tubes with foam filling had improved energy absorption and load‐carrying capacity as compared to the tubes with only the hybrid. Moreover, absorption energy was also enhanced by increasing the thickness of the foam filling 40 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the tubes with foam filling had improved energy absorption and load‐carrying capacity as compared to the tubes with only the hybrid. Moreover, absorption energy was also enhanced by increasing the thickness of the foam filling 40 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, absorption energy was also enhanced by increasing the thickness of the foam filling. 40 Kim et al studied the epoxy-based circular tubes constructed from carbon, Kevlar, and carbon-Kevlar hybrid fiber composites. 41 They investigated the failure modes and energy absorption capacities of these tubes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Extensive literature exists regarding the utilization of advanced FEA tools for modeling composite structures. Abaqus/Explicit 3 and LSDYNA have extensively employed FEA tools for simulating the dynamic axial crushing behavior of composite tubes. While there are limited options when it comes to simulating the crash response, LSDYNA stands out as a prominent and extensively utilized FEA package for nonlinear transient analysis of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, because related research might consume a significant amount of financial resources and manpower, finite element analysis (FEA) should be applied and assisted in the study. 30,31 In this paper, a series of biomimetic CFRPs with high adhesive strength and heat resistance was designed and prepared by T700 and 3234 epoxy resin. The effect of their overlapping length on tensile strength and pseudoductility was researched through experimental and simulation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Much advance on the performance prediction and structural optimization of discontinuous laminates has been gained by the previous studies. Besides that, because related research might consume a significant amount of financial resources and manpower, finite element analysis (FEA) should be applied and assisted in the study 30,31 …”
Section: Introductionmentioning
confidence: 99%